The sports cardiology team: personalizing athlete care through a comprehensive, multidisciplinary approach - Van Hattum, J.; Verwijs, S. M.; Spies, J. L.; Boekholdt, S. M.; Groenink, M.; Panhuyzen-Goedkoop, N. M.; Senden, P. J.; Willems, A. R.; Knobbe, I.; Blom, N. A.; Wijne, C. A. C. M.; Crabben, S. N.; et al. (European Heart Journal, 2021)
Background/Introduction: Multidisciplinary teams (MDT) are an integral part of cardiology. In sports cardiology wide area of expertise is required to differentiate between extraordinary pathophysiological adaption and pathology. In Addition, expertise-based sports advice should be prescribed with great care considering the great impact on (professional) sports careers. Specific guidelines for the composition of MDT's for sports cardiology are currently lacking. We established a sports cardiology MDT in April 2020 (Amsterdam UMC), consisting of experts in the fields of sports medicine, cardiogenetics and paediatric cardiology, cardiovascular imaging and electrophysiology, with bi-monthly meetings. Cases were contributed from cardiologists or referred nationally for expertise with patients/athletes varying from recreational to elite-level sports. Purpose: To describe our infrastructure and utilization of a sports cardiology MDT, and to justify the need for a sports cardiology MDT. Methods: We retrospectively analysed all MDT reviewed cases (from April 2020 to April 2021), and collected follow-up data 1 year after initial MDT review. Data were classified according to type/level of sports. We compared diagnosis and/or reason for referral and sports advice at initial MDT application and after panel review. In addition we abstracted data on occurrence of cardiac symptoms and/or cardiac events, and adherence to sports advice. Results: 112 cases underwent MDT review, with a mean age of 32 (SD 16.0) years. In total 12% were women, 38% professional athletes, and 30% engaged in high dynamic/low static sports. Reasons for referral were personalised sports advice in 48%, expert opinion in 28%, and abnormal ECG/CMR/CPX in 24%. The diagnosis was revised in 55% (n=61), main groups; 1) suspicion of (non-specified) cardiomyopathy (CMP) to no cardiac pathology in 20% (n=12), and 2) "cardiac abnormalities with no clear diagnosis" to "no cardiac pathology" in 36% (n=22) (Figure 1). Sports advice was revised to more personalized sports advice in 30% (n=34) (Figure 2), main groups; no restriction to no peak load/specific maximum load in 38% (n=13), and no restrictions to no competitive sports in 26% (n=9). At 1 year follow-up, the (sports) advice was adhered in 99,98% (n=111), and cases with no sports restrictions reported no cardiac symptoms in 99% (n=72/73), and no major acute cardiovascular events in 100% (73/73). No further revisions of diagnoses were found to have taken place. Conclusion: Our experience with a comprehensive, sports cardiology MDT demonstrates that such an approach is feasible, and leads to more personalised treatment- and sports advice in athletes. Medium-term adherence to sports advice given is high. A team-based approach also leads to a higher percentage definitive diagnoses. Our findings serve as a proof-of-concept of the added value of the sports cardiology team in care for athletes and patients who wish to engage in sports and exercise.